CITIZEN SCIENCE AND SCIENTIFIC COMMUNICATION: WHAT, WHEN, WHERE AND HOW TO INFORM AND WHO SHOULD COMMUNICATE ABOUT LONG COVID. - García Carrizo, Jennifer; Gertrudix, Manuel (Revista de Comunicación y Salud, 2025)
Introduction: The lack of adequate health information, especially during crises such as COVID19, creates distrust and misinformation, which negatively impacts public health and medical care. Long COVID patients face scepticism, highlighting the urgency of improved communication and research to support their recovery. Methodology: Structured interviews with 42 Long COVID patients, 10 healthcare professionals, and 11 health communication specialists to obtain a comprehensive picture of the situation and develop recommendations. Results: The need for institutional recognition of Long COVID is emphasized. The creation of official digital platforms and increased awareness among primary care physicians is suggested. The importance of collaboration between government bodies, associations, patient groups, and communication experts is emphasised to provide multidisciplinary and transparent information, considering the evolution of scientific research. Discussion: Improving the communication and recognition of Long COVID can reduce misinformation and distrust. Collaboration between actors is key to ensuring effective and accurate information dissemination. Scientific communication actions, such as conferences and reports, are significant steps to raise awareness among society and health professionals about Long COVID. Conclusions: It is crucial to optimize the dissemination of information about Long COVID via official digital platforms and increase medical awareness. Multidisciplinary collaboration and scientific communication activities are essential to support patients and improve public health.